ANALISIS DAMPAK PERTUMBUHAN PASAR MODEREN TERHADAP EKSISTENSI PASAR TRADISIONAL DI KABUPATEN BEKASI - Rusham - (Optimal: Jurnal Ekonomi dan Kewirausahaan, 2016)
The emergence of modern retailers (supermarket, minimarket and department stores) in the early 1980s didThe emergence of modern retailers (supermarket, minimarket and department stores) in the early 1980s did not threaten the traditional market. However, the modern retail of consumer targeting the upper middle class, as an alternative to the more traditional markets that are identical to the slum, with the look and quality of the goods is poor, and the low sale price and conventional bargaining system. 2000s, several locally owned conglomerate retailers anticipate threats and invasion of foreign retailers to shift to indirect competition, to develop a mini market format, the number of outlets operated has reached about 2,200 outlet. Factors that influence positively and significantly to the growth of the modern market in Bekasi are population, number of households and the level of income per capita. The increase in population, number of households, and income per capita in Bekasi causing increasing number of modern market. In general, this study is expected to provide information that is accurate enough for the Bekasi government in formulating a comprehensive policy-related programs and activities that are recommended for the development of traditional traders in Bekasi, and to develop regulatory models suitable for traditional and modern Traders in Bekasi district, because the government may not prohibit large retailers to enter the retail business sector